Research and insights for application of CO2-ECBM technology in deep high-rank coal seams: a case study of Jinzhong block, Qinshui Basin - Yongwang ZHENG; Yinan CUI; Xin LI; Cui XIAO; Tao GUO; Dengfeng ZHANG (Shiyou shiyan dizhi)
Deep high-rank coal seams have significant resource potential, but exhibit characteristics of "strong adsorption and weak desorption", making it challenging to effectively utilize with conventional development methods. Compared with other enhanced recovery technologies such as chemical flooding and thermal flooding, CO2-ECBM (CO2 geological sequestration-Enhanced Coal Bed Methane Recovery) technology offers dual benefits of energy conservation and emission reduction, and increased recovery rates of coalbed methane. In order to clarify the characteristics of CO2 adsorption and desorption, demonstrate the feasibility of CO2-ECBM technology in enhancing the recovery of deep high-rank coalbed methane, and help release the productivity of deep high-rank coalbed methane, this study focused on the Jinzhong block, Qinshui Basin, and conducted experimental research on the CO2 adsorption and desorption characteristics of deep high-rank coal seams. The research results showed that the adsorption capacity of CH4 in coal seams increased gradually with rising equilibrium pressures. In contrast, the adsorption capacity of CO2 in coal seams initially increased, then sharply dropped near the critical pressure, followed by a significant rise, which was influenced by the pore and fracture development characteristics of the coal seams and the properties of CO2. The adsorption capacity of CO2 in deep high-rank coal seams was about 2 to 5 times that of CH4, and the adsorption capacity of supercritical CO2 in coal seams was stronger. The sensitive desorption pressure of CO2 was 3/4 of that of CH4. Once adsorbed in coal seams, CO2 showed an obvious adsorption/desorption lag, with a large proportion of CO2 remaining in coal seams in the form of adsorbed storage and residual storage, which provided favorable conditions for large-scale CO2 storage and CH4 replacement. Through the analysis of experimental results, it was clear that developing CO2-ECBM in deep high-rank coal seams was feasible and could significantly enhance coalbed methane recovery. In field application, the pressure level of gas reservoir could be increased through methods such as advanced gas injection and increasing injection pressure, thereby enhancing competitive adsorption efficiency. Additionally, the low sensitive desorption pressure indicated a high backflow rate after CO2 injection, suggesting that CO2 recycling should be considered.